GPU Pro 4 : advanced rendering techniques - Engel, Wolfgang F. (CRC Press, Taylor & Francis Group, 2013)
"With by section editors drawn from a variety of areas in rendering techniques, especially as concerns interactive media and games, this book covers advanced techniques that run on the DirectX or OpenGL run-times, or any other run-time with any language available. It includes topics such as geometry manipulation, rendering techniques, handheld devices programming, effects in image space, shadows, 3D Engine Design, and graphics related tools, environmental effects. The book contains a dedicated section on General Purpose GPU Programming that covers CUDA, DirectCompute and OpenCL examples"--